1926
DOI: 10.1051/jcp/1926230733
|View full text |Cite
|
Sign up to set email alerts
|

Travaux du bureau international d’étalons physico-chimiques

Abstract: Ce travail a pour but de faire connaître les méthodes en usage au Bureau international d'Etalons physico-chimiques, pour la préparation des liquides organiques purs et l'étude de leurs constantes. Après avoir précisé la notion d'espèce chimique pure, les auteurs indiquent les modes de purification qu'ils ont suivis et les critères de pureté employés ; ils font connaître les détails opératoires permettant d'apprécier la précision de leurs mesures de températures, de volumes, d'indices, et de viscosité et termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1930
1930
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The viscosity of 2MB at 15°C, 0.234 cP, 28 is quite similar to that of its isomer n-pentane at the same temperature ͓0.241 cP Ref. 29͔.…”
Section: Emission In 2mbmentioning
confidence: 73%
“…The viscosity of 2MB at 15°C, 0.234 cP, 28 is quite similar to that of its isomer n-pentane at the same temperature ͓0.241 cP Ref. 29͔.…”
Section: Emission In 2mbmentioning
confidence: 73%
“…As an illustration, the following example may be reported. Benzene saturated with water at 25° C contains aroun~ 0.1 percent of water and has a refractive index lower by 0.000 14 than benzene, water-free, whereas a change in temperature of 1°C causes a change in the refractive index nif of 0.00063 [20]. From all of the measurements made, the refractive index of benzene at 25° C for the sodium line D may be taken as 1.49807 ± 0.00006.…”
Section: T Ab Le I -Properties Of the Preparations Of Benzenementioning
confidence: 99%
“…THE best cyclohexane available through most of the leading chemical dealers has a freezing point between 3.5°and 4.5°C. Timmermans (13) and others have shown that the freezing point of the pure substance lies close to 6.4 °C. Since the physicochemical properties of the hydrocarbon make it a useful solvent for many purposes, a simple method of purification seemed highly desirable.…”
mentioning
confidence: 87%